FLEXIBILITY EVALUATION IN PRACTITIONERS OF RHYTHMICAL GYMNASTICS (Fiep Bulletin - online, 2014)
The present study had as goal evaluate gymnasts' flexibility who make part of the Center of High performance of State of Amazons, in Manaus, through Test battery tests of Ilia Vankov, approved by the gymnasts' Bulgarian Federation. By the test results 3 (flexibility) can verify that just 53 gymnasts -45, 29% -own good hip articulation flexibility. Most of them- 54, 70%- did not manage to reach the established minimum exigency. Being the flexibility one of the physical qualities demanded most in the practice of the Rhythmical Gymnastics, it can conclude that the gymnasts choice process was not made through tests and that maybe for this reason the team has few gymnasts with flexibility maxim.
Keywords: Flexibility; rhythmical gymnastics; physical tests